Sintering-free preparation of porous ceramsite using low-temperature decomposing pore former and its sound-absorbing performance. (20th May 2018) - Wu, Huiqin; Zhang, Teng; Pan, Rongjun; Chun, Yeyang; Zhou, Hongmei; Zhu, Wanxu; Peng, Hanze; Zhang, Qing
Highlights: Ceramsite is a good sound absorbing material. Heating rate, foaming agent addition amount, curing time to achieve control. Ceramic micro-hole structure determines its sound absorption properties. Abstract: Porous ceramsite features excellent sound-absorption performance which is governed by the pore characteristics, such as pore size, apparent porosity, and interconnected pore network. In this work, porous sound-absorption ceramsite with different apparent porosities was prepared by using ammonium hydrogen carbonate as pore former. The effects of pore former dosage, heating rate, and curing time on the microstructure of the obtained ceramsite were investigated. The results revealed that the pore size and apparent porosity increase as a function of the pore former dosage and heating rate, respectively; whereas decrease as a function of curing time. For the ceramsite without curing, a maximum apparent porosity of 32.67% could be reached under a pore former dosage of 2.0% and a heating rate of 20.0 °C/min; however, for those cured for 72 h, the maximum apparent porosity was estimated to be only 27.43%. The sound-absorption performance correlated positively with the apparent porosity, whereas the growth and decline of pore size resulted in fluctuation of sound-absorption coefficient within the frequency rang of 200–2000 Hz because the linear flow resistance and the air friction increase with the decrease of the pore diameter.